PTU-047 Acetic acid guided focal endoscopic resection without rfa remains an effective treatment for barrett's neoplasia: time to reassess the role of rfa?. (22nd June 2015) - Chedgy, FJQ; Basford, P; Bhattacharyya, R; Kandiah, K; Bhandari, P
Abstract : Introduction: Endoscopic resection (ER) is an established effective treatment for Barrett's neoplasia. ER can lead to recurrence due to residual neoplasia left behind, so it is suggested that all patients should undergo radiofrequency ablation (RFA) after ER. Acetic acid chromoendoscopy has been shown to be an effective method of localising and delineating dysplastic areas of Barrett's oesophagus and we aim to review the outcome of Acetic Acid guided focal ER without RFA in our patients. Method: All ER procedures between January 2005 and November 2014 were recorded in a prospective database which was analysed. Acetic acid guided focal ER was the treatment strategy with the aim of removing all neoplasia visible with acetic acid chromoendoscopy. RFA was not used in this group. Results: 112 patients were treated for dysplastic Barrett's oesophagus or early Barrett's cancer by ER. The mean age at first procedure was 68 years and 82% of the patients were male. Mean initial Barrett's length was 5.1 cm. 35 of 112 patients had advanced histological features on the initial ER specimen and were referred for radical cure. The remaining 77 cases showed; intramucosal cancer (IMC) in 46, high grade dysplasia (HGD) in 28 and low grade dysplasia in 3. All 77 cases have follow-up data with a mean duration of 5.4 years. 67 of 77 cases (87%) have sustained eradication of HGIN/IMC after focal ER. 10 patients (13%) developed further neoplasia during follow up. 5/10 patients (6.5%) developed invasive cancer in the residual Barrett's, all were diagnosed endoscopically and successfully managed with radical curative treatment. Focal ER was successful in a mean of 1.3 procedures per patient (range 1–3). Complication rate was 4% (4 bleeds, 2 strictures). No additional RFA was performed in this patient group. Table 1 compares our outcomes with UK HALO registry outcomes where all patients receive RFA. Conclusion: Acetic acid guided ER is an effective and safe treatment for dysplastic Barrett's oesophagus. Progression to cancer after acetic acid guided ER is equivalent to the reported rate of progression after EMR+RFA. 1 Equal rates of sustained eradication of HGIN/IMC are achieved. An acetic acid+ER strategy is potentially much cheaper than an ER+RFA strategy. This data calls for a better stratification of patients who require RFA after ER. Disclosure of interest: None Declared. Reference: Haidry, et al . Gastroenterology 2013;145 :87–95